Posted by Jeromino on Thursday, March 31, 2011 at 5:02am.
(gof)(x) means you substitute the whole expression of f(x) to g(x):
(gof)(x) = g(f(x)) = f(x) + 1
(gof)(x) = x + 1
for #2, we do the same,, we substitute f(x) to f(x):
(fof)(x) = f(x)
(fof)(x) = x
hope this helps~ :)
math - Find a. fog b. gof c. fof d. gog for each function f(x)=4-x g(x)=3x-5
college algebra - 1. answer the following for the given quadratic function f(x)=...
math - Find a. fog b. gof c. fof d. gog f(x)=4-x g(x)=3x-5
math - (x) =pi/2-x g(x)= 5sinx/8+cos x find (gof)(pi/2) and (fof)(pi/2)
precalc - f(x) =pi/2-x g(x)= 5sinx/8+cos x find (gof)(pi/2) and (fof)(pi/2)
Calculus - Hi there, I need help with composition of functions. I need to find ...
college algebra - 1.for the given function f&g, find the following and state...
math/calculus - let f(x)=ln(x)x>0 let k(x)= f(g(x)) and m(x)= f(g(x)) a) ...
calcius - Determine whether the relation represents a function. If it is a ...
math - questions involving domain and range... 1. Find the domain of the ...
For Further Reading